Law of Included Infinitely-Many-Middles within the frame of Neutrosophy - Smarandache, Florentin (Neutrosophic Sets and Systems, 2023)
In this paper, we extend, for the first time, the Law of Included Multiple-Middles to theLaw of Infinitely-Many-Middles. And we present several practical applications. Also, we discussAristotle's Syllogism, Principle of Identity, and Principle of NonContradiction.